2016
DOI: 10.1155/2016/3287381
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Growing Meningioma in a Woman Undergoing Fertility Treatments

Abstract: Meningiomas have long been known to be associated with sexual hormones. We discuss here the case of a woman with a huge meningioma that rapidly grew over the course of a couple years while the patient was simultaneously taking fertility treatments. There is substantial evidence suggesting that fertility treatments can fuel the growth of meningiomas. The potential risks should be considered in women with a previous or family history of meningiomas who plan to undergo fertility treatment. These patients need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Interrogation of the SE landscape implicates PR as a core transcriptional driver of a subset of tumors. These data provide a putative explanation for the strong epidemiologic sex bias and case reports of meningiomas receding following discontinuation of progesterone agonists (3)(4)(5)(6)(7). The uneven responses reported in clinical trials may thus be driven by distinct epigenetic subgroups of tumors.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Interrogation of the SE landscape implicates PR as a core transcriptional driver of a subset of tumors. These data provide a putative explanation for the strong epidemiologic sex bias and case reports of meningiomas receding following discontinuation of progesterone agonists (3)(4)(5)(6)(7). The uneven responses reported in clinical trials may thus be driven by distinct epigenetic subgroups of tumors.…”
Section: Discussionmentioning
confidence: 82%
“…Grade I tumors affl ict female over male patients at a 3:1 ratio, a predilection that is lost in highergrade tumors ( 1 ). Case reports and small studies have implicated progesterone agonists in meningioma growth, with reports of tumor regression following discontinuation of exogenous progesterone ( 3,4 ). However, clinical trials have demonstrated inconsistent results, and predicting responders to hormone therapy remains a signifi cant challenge (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…While studies investigating meningioma and fertility treatment are limited to retrospective case reports and one case-control study [10][11][12][13], the association of progesterone receptor expression and meningioma has been studied more extensively [30]. There are various situations in addition to fertility treatment where patients might be exposed to high dose estrogen or progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…One large case control study found no association between fertility treatment and meningioma [10]. There have been three cases of meningioma diagnosed in women with a history of fertility treatment described in the literature [11][12][13]. Recently, Wengel et al identified eight transgender patients who developed meningioma during hormone therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Korhonen et al (18) the fertility treatments did not influence the risk of meningioma. Three single case reports describe meningiomas diagnosed in women with history of fertilization (41)(42)(43). In the study of Shahin et al (44), the group of female patients with meningioma and history of fertility treatment had significantly younger age and higher rate of multiple non-skull base meningiomas as compared to the group with no fertility treatment.…”
Section: Fertility Therapiesmentioning
confidence: 99%